The assessment of total energy expenditure during a 14-day in-season period of professional Rugby League players using the doubly labelled water method - Morehen, J. C.; Bradley, W. J.; Clarke, J.; Twist, C.; Hambly, C.; Speakman, J. R.; Morton, J. P.; Close, G. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Rugby League is a high-intensity collision sport competed over 80 min. Training loads are monitored to maximize recovery and assist in the design of nutritional strategies although no data are available on the total energy expenditure (TEE) of players. We therefore assessed resting metabolic rate (RMR) and TEE in six Super League players over 2 consecutive weeks in-season including one game per week. Fasted RMR was assessed followed by a baseline urine sample before oral administration of a bolus dose of hydrogen (deuterium 2H) and oxygen (18O) stable isotopes in the form of water (2H218O). Every 24 hr thereafter, players provided urine for analysis of TEE via DLW method. Individual training load was quantified using session rating of perceived exertion (sRPE) and data were analyzed using magnitude-based inferences. There were unclear differences in RMR between forwards and backs (7.7 ± 0.5 cf. 8.0 ± 0.3 MJ, respectively). Indirect calorimetry produced RMR values most likely lower than predictive equations (7.9 ± 0.4 cf. 9.2 ± 0.4 MJ, respectively). A most likely increase in TEE from Week 1 to 2 was observed (17.9 ± 2.1 cf. 24.2 ± 3.4 MJ) explained by a most likelyincrease in weekly sRPE (432 ± 19 cf. 555 ± 22 AU), respectively. The difference in TEE between forward and backs was unclear (21.6 ± 4.2 cf. 20.5 ± 4.9 MJ, respectively). We report greater TEE than previously reported in rugby that could be explained by the ability of DLW to account for all match and training-related activities that contributes to TEE.